PERANAN ISTRI NELAYAN DALAM MEMBANTU MENINGKATKAN PENDAPATAN KELUARGA DI DESA BABULU LAUT KECAMATAN BABULU KABUPATEN PENAJAM PASER UTARA - Anwar Sadat; Elly Purnamasari; Qoriah Saleha (2339-1324, 2018)
The purpose of this research was determined the role of fisherman’s wife based on productive activity and contribution to increase family fisherman’s family income, the income different of fisherman’s family which the fisherman’s wife involved or not on productive activity and identified the factor that motivate the wife involve in productive activities. The research was conducted since February until September 2017 in Babulu Laut Village, Babulu Subdistrict, Penajam Paser utara. the Sampling method was stratified random sampling to 30 respondents. The data was applied by analysed by various methods that are descriptives analysis, calculation of average income and multiple linier regression. The result was obtained the role of fishermen's wife on productive activity were fish crackers and salt fish production, seashell collectors, seller of basicneeds of ice, clothes and fried food, village office employee and teacher. The income contribution of fishermen's wife in family income was Rp. 39.211.472 per month (39.2%), that are smaller than husband's income Rp. 60.805.667 per month (60.8%). The income contribution of fisherman’s wife who is warking on productive activities were Rp.6.667.809 per month, bigger than the family income with wife not warking or productive activite, that are Rp. 4.892.983 per month. The factors that are age, education level, numbers of family member, Husband's income and bussiness’s vision not influenced significantly, both parsially or simultaneously.